PENGARUH DIVIDEN DAN STATUS PEMBAYARAN DIVIDEN TUNAI TERHADAP KUALITAS LABA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada tahun 2010-2014) - Ardhyayuda Patria Mahari; Agus Purwanto (Diponegoro Journal of Accounting, 2016)
The objectives of this study are to obtain empirical proof and analyze dividends’ effect views from several dividends proxies. The dividends proxies are from dividends payment status, size of dividends, the increase of dividends size, and the persistence of dividends distribution towards company’s earnings quality.The population of this study are manufacturing companies listed in Bursa Efek Indonesia (BEI) from 2010 - 2014. Total sample used in this study are 72 companies based on predetermined criteria (purposive sampling). Data was analyzed using descriptive statistical analysis, classic assumption test, multicoloniarity test, and hypothesis testing with multiple regression analysis.Results of this analytical study indicate that cash dividends payment status has a significant positive effect on the companies’ earnings quality, the dividends size and the increase of dividends size also have a significant positive effect on the earnings quality, however persistence of dividend distribution has no significant effect on the company’s earnings quality.